Renegotiations of the southeast asian female identity through identity fluidity and transculture/ality in selected novels by Minfong Ho - Shamsuddin, Syamsina Zahurin (2021)
Previous studies on Southeast Asian females have focused mostly on issues pertaining to their identity viewed by the West as voiceless, submissive and hypersexual, which have also affected their personal growth and developments. This study problematises these mainstream notions by the West and investigates whether they are reflected in works of fiction through the portrayals of female protagonists living in Southeast Asia, namely in Thailand and Cambodia, in four novels by the American-Chinese writer, Minfong Ho. In the scope of this study, these female protagonists are portrayed as subjected to the expectations of how they should behave in societies and conform to the patriarchal values ingrained in these cultures. Thus, the three concepts of identity fluidity and the decentring of subject by Stuart Hall, and the concept of transculture/ality by Arianna Dagnino are applied as conceptual frameworks to investigate the Southeast Asian female identity in Sing to the Dawn, (1975), Rice without Rain (1986), The Clay Marble (1991), and The Stone Goddess (2003) as the data for this study. The research objectives are to explore how the three concepts of identity fluidity, namely the enlightenment subject, the sociological subject, the postmodern subject, and the decentring of the subject through transculture/ality are reflected in the novels through the female protagonists’ practice of traditional cultures in the Thai and Cambodian societies; to examine how the identities of the female protagonists, as young women living in traditional patriarchal Thai and Cambodian societies constrained within power imbalance and gender relations, are shaped through the decentring process by transculture/ality; and to discover the female protagonists’ various responses to the practice of traditional cultures in Thai and Cambodian societies by applying the tenets of transculture/ality. The methodology of the study is based on a textual analysis of the female protagonists’ behaviours, thoughts, and speeches, in relation to identity fluidity and transculture/ality by focusing on how they undergo the three stages of identity fluidity and the decentring process of transculture/ality with regards to their Southeast Asian female identities as Thai and Cambodian women. The findings reveal that the protagonists’ identities gradually evolve from being conformed to the practice of their Thai and Cambodian cultures to young women who exhibit voice, agency and no hypersexual characteristics after being decentred through the intermingling of cultures and demonstrating the three stages of identity fluidity. More specifically, Dawan in Sing to the Dawn fulfils her wish to study in Bangkok when she firmly stands by her decision to study there, Jinda in Rice without Rain transforms into a reformation activist when she journeys to Bangkok to fight for her father’s release from prison, Dara in The Clay Marble becomes the head of the family when she resolutely convinces her brother to leave the Cambodian camp and start anew, and Nakri in The Stone Goddess breaks her silence as she openly mourns after fleeing from the Khmer Rouge regime. Findings from this study suggest that identity fluidity and transculture/ality can further be studied in light of the third space concept and liminality.